The family Romanov : murder, rebellion & the fall of Imperial Russia - Fleming, Candace; Schwartz & Wade Books (New York : Schwartz & Wade Books, 2014)
When Russia's last tsar, Nicholas II, inherited the throne in 1894, he was unprepared to do so. With their four daughters (including Anastasia) and only son, a hemophiliac, Nicholas and his reclusive wife, Alexandra, buried their heads in the sand, living a life of opulence as World War I raged outside their door and political unrest grew into the Russian Revolution. Maneuvering between the lives of the Romanovs and the plight of Russia's peasants and urban workers -- and their eventual uprising -- Fleming draws a poignant portrait, complete with period photographs and primary source material.
Before you begin -- Russia 1903 -- Beyond the palace gates : peasant turned worker -- Before the storm -- "I dreamed that I was loved" -- Beyond the palace gates : a peasant boyhood -- "What a disappointment!" -- Beyond the palace gates : lullabies for peasant babies -- "A small family circle" -- Beyond the palace gates : another family circle -- Dark clouds gathering -- The year of nightmares -- Lenin, the Duma, and a mystic named Rasputin -- Beyond the palace gates : house no. 13 -- "Pig and filth" and family fun -- Beyond the palace gates : an occupation for workers' daughters -- Gathering clouds -- Three centuries of Romanovs -- Beyond the palace gates : a different kind of education for a different kind of boy -- The storm breaks -- "My God! My God! What madness!" -- In defense of mother Russia -- Beyond the palace gates : Vasily's diary -- The reign of Rasputin -- It all comes tumbling down -- Beyond the palace gates : molecule in a storm -- "Ye tyrants quake, your day is over" -- Beyond the palace gates : "ye tyrants quake, your day is over" -- Final days -- "Survivors of a shipwreck" -- Beyond the palace gates : the "Tsar's surprise party" -- Into Siberia -- Beyond the palace gates : swarming the palace -- The house of special purpose -- Deadly intent -- "The world will never know what has become of them" -- Beyond the palace gates : life under Lenin.
Includes bibliographical references (pages 256-265) and index.
Ages 12-17.
950
Accelerated Reader
Robert F. Sibert Informational Book Award Honor Book (2015); YALSA Award for Excellence in Nonfiction for Young Adults Award Finalist (2015)
Boston Globe/Horn Book Nonfiction Award, 2015
Keywords: Romanov, House of -- Juvenile literature; Nicholas -- II, -- Emperor of Russia, -- 1868-1918 -- Family -- Juvenile literature; Nicholas -- II, -- Emperor of Russia, -- 1868-1918.; Russia -- History -- Nicholas II, 1894-1917 -- Juvenile literature; Soviet Union -- History -- Revolution, 1917-1921 -- Juvenile literature; Russia -- History -- Nicholas II, 1894-1917.; Romanov, House of; Russia -- History -- Nicholas II, 1894-1917.; Soviet Union -- History -- Revolution, 1917-1921.; Dynastie des Romanov -- Ouvrages pour la jeunesse; Russie -- Histoire -- 1894-1917 (Nicolas II) -- Ouvrages pour la jeunesse; URSS -- Histoire -- Ouvrages pour la jeunesse; Russie -- Histoire -- 1894-1917 (Nicolas II); YOUNG ADULT NONFICTION -- Biography & Autobiography -- Historical; YOUNG ADULT NONFICTION -- Biography & Autobiography -- Political; YOUNG ADULT NONFICTION -- History -- Europe; Nicholas -- II, -- Emperor of Russia, -- 1868-1918.; Romanov, House of; Families; Russia; Soviet Union; 1894 - 1921; Nicholas -- II, -- Emperor of Russia, -- 1868-1918 -- Family; Romanov, House of; Russia -- History -- 1900-1917.; Russia -- History -- 1917-1921, Revolution; Russia -- History -- 1917-1991, Soviet Union; Young adult literature; collective biographies; Juvenile works; Biographies; History; Biographies; Dust jackets (Bindings) -- 2014.; Biographies; Young adult nonfiction; NonFiction; Historical -- Royals